Penerapan Metode Kerja Kelompok Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas V Sd Negeri 003 Bangun Purba Tahun Pelajaran 2015 / 2016 - Mariati Mariati (Indonesian Journal of Basic Education, 2018)
One of the teacher's efforts in increasing proportionalism, the teacher must be willing and able to carry out improvements in learning as a correction tool for teachers in carrying out the learning process, to improve themselves in teaching, improvement of learning is carried out after the teacher finds problems that arise in the learning process in class mathematics subjects V sermester two at SDN 003 Bangun Purba, namely low student learning outcomes in mathematics subjects, as for the purpose of this study is to improve student learning outcomes in mathematics subjects. The time of this research consisted of two cycles of cycle 1 and cycle 2, silus 1 on Monday April 11 2016 and the second cycle on April 22, 2016. The learning outcomes of students in cycle 1 still got a lot of grades under the KKM. In the second place there were many who had above the KKM, because the teacher had used the right media and the teacher had applied the group work method and the students' absorptive results on the student scores 68.47, on the second cycle the average score of the children was 88 91 has been very good, thus the application of group work methods can improve the learning outcomes of SDN 003 Bangun Purba students